(untitled) (Research, Society and Development, 2022)
The adipose tissue is an important energy source for the human body. It is also a critical source of biomolecules with pro and anti-inflammatory functions, known as adipocytokines, such as leptin and adiponectin, respectively. These hormones suffer variations in activity along with adipose tissue excess. Normal concentrations of leptin inhibits appetite, decreases blood sugar, increases fatty acid oxidation, and therefore, decreases body fat. Obese individuals shows high leptin concentration, but no ligand-receptor activity. Adiponectin, in normal concentrations, shows insulin sensibilization, oxidation of muscular, vascular and other organs fatty acids, by the adiponectin receptors 1 and 2 (adipoR1 and adipoR2), cadherin-T and signalling pathways. This hormone has an opposite expression pattern than leptin, being underexpressed in obese individuals. Both hormones are deregulated in obese individuals, showing several chronic inflammation signals on adipose tissue, such as mitochondrial dysfunction, excess of saturated fatty acids, etc. All these factors corroborate to a low quality systemic environment, inducing endocrine system failures, which contributes development of cardiovascular diseases, cancer, type 2 diabetes, hepatic steatosis, and atherosclerosis. The objective of this work is to show the impact of leptin and adiponectin deregulation in obese individuals through systematic literature review.